A pragmatic per-device licensing scheme for hardware IP cores on SRAM-based FPGAs - Zhang, Li (2015)
The modus operandi of the upfront intellectual property (IP) licensing model is impractical for the developers of small to medium volume of field-programmable gate array (FPGA)-based applications. The FPGA IP market is in dire need for a more competitive and secure IP licensing scheme to flourish. In this paper, a pragmatic security protocol that could support the licensing of IP cores on a per-device basis without the need for a contractual agreement of an external trusted third party, large bandwidth, and complicated flow of communications is proposed. Besides assuring that the incentives of all stakeholders involved in the FPGA IP core trading are not scarified if not enhanced, the proposed protocol guarantees total secrecy and integrity of licensed IP cores based on available primitives of contemporary SRAM-based FPGA devices. It also prohibits the implementation of protected IP cores on unscreened excess devices and counterfeit chips sold in the gray market. The adoption of IP fingerprinting further deters the IP licensees from abusing the IP cores. Using the self-reconfiguration feature of FPGAs today, the resources consumed by the control module used for the implementation of protected IP cores on the authorized device are temporary and marginal.